Training Effectiveness and Work Motivation on Employee Performance: The Mediating Effect of Job Satisfaction - Althon Karaman Pongtuluran; Jens Batara Marewa (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The increasing complexity and volatility of the global extractive industry have made employee performance a critical determinant of organizational sustainability, particularly in technology-intensive mining companies. This study investigates the mechanical influence of training effectiveness and work motivation on employee performance, positioning job satisfaction as a pivotal mediating factor. Utilizing a quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM), data were garnered from 354 validated respondents across mining and smelting sites via structured questionnaires. Empirical findings demonstrate that both training effectiveness and work motivation exert a positive and significant impact on employee performance. Notably, job satisfaction was identified as the most dominant predictor and a partial mediator that substantively amplifies the impact of managerial interventions on operational outputs. The inner model evaluation confirms a robust predictive power of 72.4%, asserting that production efficiency in the extractive sector depends not merely on technological sophistication but is fundamentally determined by the emotional validation and psychological well-being of the workforce. This study provides strategic implications for organizational leaders to integrate satisfaction metrics into competency development programs to ensure long-term performance resilience.